Integration of Islamic Law Regulation and Positive Law in Addressing Business Ethics Challenges in The Era of Industrial Revolution 4.0 and Society 5.0 - Adisurya, Adisurya; Mansur, Mochamad (CV. Publikasi Indonesia, 2024)
The era of the Industrial Revolution 4.0 and Society 5.0 has brought significant changes in various aspects of life, including in the business world. The rapid development of technology and the integration of cyber-physical systems have changed the way businesses are conducted, giving rise to new and complex business ethics challenges. The normative juridical research method is employed in this study, which focuses on positive legal regulations related to legislation. Two approaches, the Statute Approach and the Conceptual Approach, are utilized. Primary and secondary legal sources are employed to understand and apply the law. Integrating Islamic Law and Positive Law regulations refers to the effort to combine their principles harmoniously. This integration involves identifying similarities and differences, considering contemporary aspects such as technology and globalization. Ethical challenges in business during the Fourth Industrial Revolution and Society 5.0 era include ensuring justice, sustainability, and humanity in business practices. Islamic and Positive Law regulations, such as usury and consumer protection prohibition, help guide ethical business behavior. Integrating Islamic and Positive Law regulations can address business ethics challenges. Collaboration among the government, society, and Islamic organizations is necessary to strengthen regulatory implementation. Education on Islamic values-based business ethics also needs to be reinforced to cultivate responsible business leaders for the future.